Role of Bone Scintigraphy in Modification and Finalization of the Pathological Staging of Carcinoma of Breast (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: The prognosis and treatment planning of carcinoma depends upon the stage of the disease. The presence of bone metastasis affects a patient’s prognosis and further treatment planning. The purpose of this study was whether bone scintigraphy by detecting skeletal metastasis can help in patient management by modification of initial pathological staging.Patients and Methods: A total of 110 patients of breast carcinoma who were referred for the early bone scintigraphy after the surgical procedure were included in this study. Bone scintigraphy was done 3 hours after 15 m Ci Tc-99m methylelene diphosphonate (MDP) intravenous injection. Images were acquired in Siemens E-cam dual head camera. Chi-Square test was used to analyze the variablesResults: Out of the total 110 patients with breast carcinoma referred to the institute after initial pathological staging nearly one third i.e. 31 (28.2%) patients had skeletal metastasis. In this study it was revealed that tumour size and nodal involvement correlated well with metastasis to bone. Skeletal metastasis was significantly (p3.0 – ≥5.0 cm and nodal involvement N2–N3(p